NILAI-NILAI SUFISME DALAM JAMAAH SHALAWAT WAHIDIYYAH DI KEDIRI DAN MALANG - Fatkhul Wahab; Ahmad Bukhori; Athiyah (Jurnal Penelitian Ilmiah INTAJ, 2017)
Among Muslim communities, love of the Prophet Muhammad embodied in a religious tradition known as shalawÄh tradition. ShalawÄh is an expression of deep gratitude for the guidance to Muslims on the right path. Sufism that emphasizes reading ShalawÄh of the Prophet Muhammad as dhikr primarily is ShalawÄh WÄhidiyah. The main purpose of ShalawÄh WÄhidiyah is to alleviate people from the shirk and return to the straight and true that by pleasing Allah. The focuses of this study are: (1) how do the precepts and values of Sufism in the Jamaat ShalawÄh WÄhidiyah? (2) How do the precepts and values are promoted and practiced by Jamaat ShalawÄh WÄhidiyah? (3) How does the experience of spirituality Jamaat ShalawÄh WÄhidiyah? This study is a qualitative study by using a naturalistic paradigm and phenomenology approach. The data were collected by in-depth interviews, participant observation, and documentary in the form of journals, magazines and so on. While the data analysis techniques include data reduction, presentation of data, the validity of the data and drawing conclusions. The results of this study indicate that: (1) ShalawÄh WÄhidiyah precepts include: a. li AllÄh, bi AllÄh; b. li al-RasÅ«l, bi al-RasÅ«l; c. li al-ghauts bi al-ghauts; d. yu'thÄ« kull dzÄ« á¸¥aqq; e. taqdÄ«m al-hamm tsumm al-hamm, fa al-faâ€™ tsumm al-fa'. The values contained in ShalawÄh WÄhidiyah Sufism, among others: taubah, ikhlÄsh, syukr, mahabbah. (2) Socialization ShalawÄh WÄhidiyah precepts are done by 1. individual, 2. packaged in a formal form as mujÄhadah nishf al-sanah and mujÄhadah kubrÄ, 3. through dreams, 4. implemented in the form of books, magazines, newsletters, and CDs. While this practice ShalawÄh WÄhidiyah carried out in different ways mujÄhadah usbÅ«'iyyah, mujÄhadah syahriyyah, mujÄhadah rubâ€™ al-sanah, mujÄhadah nishf al-sanah, and so forth. Keywords: The values of Sufism, ShalawÄh WÄhidiyah